Preparation method of electronic paste for multilayer ceramic capacitor electrode
Electronic slurry for multi-layer ceramic capacitor electrodes is prepared by phacoemulsification dispersion, grinding and dispersion, centrifugal grading, filtration, distillation and concentration, which solves the problem of uneven particle size distribution of metal powders in the prior art, and achieves efficient and uniform slurry preparation, which improves the capacitance and market competitiveness of MLCC.
Patent Information
- Application Number
- CN202411840923.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
- Estimated Expiration
- 2044-12-13
AI Technical Summary
The prior art is difficult to effectively classify and improve the particle size distribution of metal powders, resulting in low quality of MLCC electrode materials and cannot meet the market's demand for miniaturization, large capacity, high reliability and low cost.
Electronic slurry for multi-layer ceramic capacitor electrodes is prepared by phacoemulsification dispersion, grinding and dispersion, centrifugal slurry, filtration, distillation and concentration. Through these steps, particles exceeding the standard are removed, and the uniformity of particle size distribution, the yield and production efficiency of the slurry are improved.
The electronic slurry for multi-layer ceramic capacitor electrodes is achieved evenly distributed particle size, high yield and production efficiency, and good continuity after sintering and filming of the slurry layer, which improves the capacitance and market competitiveness of MLCC.
Smart Images

Figure 62ALSNVGINIQ0ZS1CWQL6V6PIPN6QHNHZWDFJDOW 
Figure AJNSCJIBADFVMP4EBA7G3KE409T0DFMRROBUQ1AX 
Figure ND3DR2UQU7XJCZRMMROMY2KXXG2TNK4MNW2J8ZLM
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of nano powder classification and slurry preparation, and in particular relates to a method and a device for preparing electronic slurry for multilayer ceramic capacitor electrodes. Background Art
[0002] In the multilayer ceramic capacitor industry, chip-type multilayer ceramic capacitors (MLCC) are composed of three parts: inner electrodes, ceramic layers, and end electrodes. The dielectric material and the inner electrodes are stacked in a staggered manner, and then sintered at high temperature to form a structure. A metal layer is then sealed at both ends of the chip to obtain a structure similar to a monolithic structure. Therefore, MLCC is often called a "monolithic capacitor."
[0003] Multilayer ceramic capacitors (MLCC), also known as chip capacitors, multilayer capacitors, stacked capacitors, etc., have the characteristics of small size, large capacitance, low loss rate when used at high frequencies, suitable for mass production, low price and high stability. The capacitance of MLCC is directly proportional to the overlapping area of the internal electrodes, the number of dielectric porcelain layers and the relative dielectric constant of the dielectric ceramic material used, and inversely proportional to the thickness of the single-layer dielectric. There are two main ways to increase the capacitance in a certain volume. One is to reduce the dielectric thickness. The lower the dielectric thickness, the higher the capacitance of the MLCC; the second is to increase the number of layers inside the MLCC. The more layers, the higher the capacitance of the MLCC.
[0004] The electrode materials of chip multilayer ceramic capacitors (MLCC) mainly include metal materials such as palladium, silver, platinum, nickel, iron, and copper. Due to the limited resources and high prices of precious metal materials such as palladium, silver, and platinum, the manufacturing cost of chip multilayer ceramic capacitors (MLCC) is greatly increased and the application field is limited; iron requires a series of complex process measures to solve its oxidation, diffusion and other problems, which increases the production cost; the electromigration rate of nickel electrodes is lower than that of precious metal electrodes, and nickel has good corrosion resistance and heat resistance, and relatively low resistivity. The corresponding MLCC manufacturing process and products are highly stable and have become one of the most widely used MLCC electrode materials; although copper paste has problems such as easy oxidation, fast shrinkage, and high electromigration rate, the above shortcomings have been gradually overcome with process improvements, and copper has the advantages of being cheaper than nickel, lower resistivity, lower sintering temperature, lower comprehensive manufacturing cost, more environmentally friendly, and longer life of finished MLCC. Therefore, in recent years, base metals such as nickel and copper are commonly used as electrode materials for chip multilayer ceramic capacitors (MLCC). With the advancement of science and technology and the development of the electronics industry, electronic devices in the market are constantly developing in the direction of miniaturization, large capacity, high reliability and low cost. MLCC thin and short series products have gradually tended to be packaged and universal. Many leading manufacturers are competing to develop large-capacity MLCCs with better profit margins. Therefore, higher requirements are placed on the electrode materials used in capacitors, so the metal particles are smaller and the particle size distribution is more uniform.
[0005] The MLCC electrode slurry preparation process is to first grade the raw metal powder to remove particles that exceed the standard, then filter to further remove the agglomerated powder and particles, and then prepare the electronic slurry, print the electrode slurry on the ceramic diaphragm, and dry it to obtain a clear and complete dielectric diaphragm. At present, domestic metal powder suppliers can only provide primary metal powder raw materials. The metal powder has a wide particle size distribution, many large particles, and serious agglomeration. It cannot be directly applied to the MLCC field. The metal powder needs to be further graded to remove particles that exceed the standard, and then prepared into electrode slurry and printed on the ceramic diaphragm for firing. Because the quality of metal powder electrode slurry directly determines the performance of the capacitor, how to improve the particle size distribution of metal powder, improve the quality of metal powder, and prepare ultrafine metal powder electronic slurry is the key to reducing the volume of capacitors, increasing capacitance and the market competitiveness of MLCC. Summary of the invention
[0006] In response to the problems raised by the background technology, the present invention studies and designs a method and a device for preparing electronic slurry for multilayer ceramic capacitor electrodes, and its purpose is to provide a method and a device for preparing electronic slurry for multilayer ceramic capacitor electrodes with uniform particle size distribution, high yield and production efficiency, and good continuity of the slurry layer after sintering and film formation.
[0007] The technical solution of the present invention: A method for preparing an electronic paste for a multilayer ceramic capacitor electrode comprises the following steps: (1) Ultrasonic emulsification dispersion Adding an organic solvent into an ultrasonic emulsification kettle, stirring, adding ultrafine metal powder to prepare metal slurry, then adding a thickener, ultrasonic emulsifying and dispersing, to prepare a mixed electronic slurry; (2) Grinding and dispersion The slurry dispersed by ultrasonic emulsification in step (1) is sent to a grinder for grinding and dispersion and then sieved to form a homogeneous emulsion; (3) Centrifugal classification The slurry after screening in step (2) is sent to a centrifuge for centrifugal classification to remove particles exceeding the standard, thereby obtaining an electronic slurry with uniform particle size distribution; (4) Filtering The electronic slurry after centrifugal classification in step (3) is sent to a filter for filtration to remove foreign matter and powder clumps; (5) Stirring and replacement The electronic slurry filtered in step (4) is added to a stirred tank after solid-liquid separation by sedimentation, and ethanol solvent is added for replacement to reduce the carbon content; (6) Distillation and concentration After adding an electronic solvent to the replaced electronic paste in step (5), the electronic paste is sent to an evaporation concentration device for concentration to obtain an electronic paste for multilayer ceramic capacitor electrodes.
[0008] Preferably, in the step (1), the ultrafine metal powder is prepared by a PVD method, and its specific surface area equivalent particle size is 30-250 nm, the ultrafine metal powder is one of nickel and copper, the organic solvent is at least one of ethanol, ethylene glycol, propanol, n-butanol, glycerol, and acetone, the thickener is lignin or ethyl cellulose (EC), and its molecular weight is 100-2000, the ultrasonic emulsification temperature is 10-25° C., the emulsification dispersion time is 0.5-3 h, and the prepared mixed electronic slurry has a viscosity of 5-45 cps and a solid content of 5-35 wt%.
[0009] Further preferably, in step (1), the ultrasonic emulsification temperature is 12-15° C., the viscosity of the prepared mixed electronic slurry is 10-25 cps, and the solid content is 7-25 wt %; the ultrafine metal powder is nickel powder, and the oxygen content of the nickel powder is 10000-55000 ppm.
[0010] Preferably, in step (2), the grinder uses 0.1-2 mm zirconium beads, the grinder speed is 300-3000 r / min, the grinding temperature is 5-45° C., the grinding time is 1.5-3 h, and the screen is 100-1000 mesh.
[0011] Preferably, the electronic slurry after screening in the step (3) is sent to a tubular centrifuge for classification by a peristaltic pump, the drum speed of the tubular centrifuge is 5000-30000 r / min, the separation factor is 15000-20000, and the electronic slurry after centrifugal classification has a DMax of 0.2-0.7 μm according to a PSD test.
[0012] Further preferably, in step (3), the drum speed of the tubular centrifuge is 10000-25000 r / min.
[0013] Preferably, the electronic slurry after centrifugal classification in step (4) is sent to a filter for filtration through a peristaltic pump, and the pore size of the filter element is 0.2-2 μm.
[0014] Preferably, the electronic slurry filtered in step (5) is added to a stirring tank, and solid-liquid separation is carried out by sedimentation, and the concentration is controlled at 30-80%, and ethanol solvent is added with a concentration of 15-50%. After stirring for 0.5-3 hours, solid-liquid separation is carried out by sedimentation, and the supernatant is removed, and ethanol solvent is added for replacement until the carbon content of the slurry is ≤2% and the slurry viscosity drops below 20cps.
[0015] Preferably, in step (6), the electronic solvent is one of DHTA, terpineol, glycerol, n-butanol and sec-butanol. After adding the electronic solvent, the concentration of the electronic slurry is 30-80wt%. The electronic slurry is distilled and concentrated under vacuum. The absolute pressure in the heating concentration kettle is 10-100Kpa. The slurry temperature in the heating concentration kettle is controlled at 50-100°C. The alcohol solvent is removed by vacuum evaporation. The residual solvent is ≤5%. The solid content of the electronic slurry is 50-75%, and the metal content is 55-75%.
[0016] Further preferably, in the step (6), the absolute pressure in the heating and concentrating kettle is 20-80 KPa, the temperature of the slurry in the heating and concentrating kettle is controlled at 50-80°C, the residual solvent content is ≤1.5%, the solid content of the electronic slurry is 55-75%, and the metal content is 60-70%.
[0017] A device used in the method for preparing electronic slurry for multilayer ceramic capacitors as mentioned above comprises, in sequence, an ultrasonic emulsification kettle, a grinder, a rotary vibrating screen, a centrifuge, a filter, a stirring kettle, and an evaporation concentration device connected by a pipeline, wherein a peristaltic pump is installed on the pipeline connecting the ultrasonic emulsification kettle and the grinder, and a peristaltic pump is installed on the pipeline connecting the rotary vibrating screen and the centrifuge.
[0018] Preferably, the evaporation concentration device comprises a heating kettle, a condenser, a storage tank, and a vacuum pump which are sequentially connected through pipelines, and the condenser can recover and reuse the evaporated ethanol vapor.
[0019] Preferably, a jacket is provided on the outer layer of the ultrasonic emulsification kettle to cool and control the emulsification temperature of the slurry in the ultrasonic emulsification kettle.
[0020] Beneficial effects of the present invention: 1) The present invention uses ultrafine metal powder with an average particle size of 50-150nm measured by BET to prepare slurry. The powder particle size is small, and the fine metal powder particles have good sintering performance, which can improve the density of the sintered film and the number of layers inside the MLCC. The more layers, the higher the capacitance; 2) The metal powder prepared by the PVD method has high sphericity (MLCC Electrode slurry requires that the metal powder for making the conductive phase needs to have round particles, uniform distribution and a certain specific surface area. Spherical particles have good packing performance, high mechanical strength and can make the sintered film structure more compact. ), spherical metal powder with uniform particle size in electrode slurry can ensure the uniformity of the conductive slurry and make the metal particles in good contact after sintering; 3) Nickel oxide powder with an oxygen content of 10000~55000ppm is selected to prepare the slurry. Nickel oxide has a high melting point (1984℃), which can prevent the metal powder from melting when sintering with the ceramic medium at the same time, and maintain the continuity of the metal slurry layer after sintering and forming the film; 4) Use tube The slurry is graded by a centrifuge, and the slurry is fed from the bottom center of the drum, eliminating the short-circuit problem of conventional grading equipment. The drum speed is 5000~30000r / min, the separation factor is in the range of 15000~20000, the grading accuracy is improved, the slurry has fewer large particles, and the overflow Dmax after classification is less than 500nm. The particle size distribution is uniform, which can prevent the occasional large particles in the powder from penetrating the dielectric layer and causing structural defects without lamination; 5) Ethyl cellulose thickener is added to the graded slurry, the slurry viscosity is 10~15cps, the powder forms a suspension, the sedimentation rate of the powder particles is reduced, the yield is increased, and the production efficiency is high; 6) The organic carrier of the electrode slurry is composed of a variety of organic solvents, and its function is to ensure the quality of electrode slurry printing. DHTA, pine oil, etc. are selected as slurry solvents, and the boiling point of the solvent is ≥200℃. The slurry preparation process is not easy to agglomerate or agglomerate. The continuity of the slurry layer after sintering and film formation is good, and the electrode and the dielectric layer are tightly combined to avoid stratification or electrode cracking. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 This is an electron microscope image of the nickel powder of Example 3 before step (3); Figure 2 This is an electron microscope image of the nickel powder of Example 3 after step (3); Figure 3 This is an electron micrograph of the nickel powder of Example 3 before step (4); Figure 4 This is an electron microscope image of the nickel powder of Example 3 after step (6); Figure 5 It is a schematic diagram of the structure of the preparation device of the present invention.
[0022] Among them: 1. pipeline, 2. ultrasonic emulsification kettle, 2-1, jacket, 3. grinder, 4. rotary vibrating screen, 5. centrifuge, 6. filter, 7. stirring kettle, 8. peristaltic pump, 9. heating kettle, 10. condenser, 11. storage tank, 12. vacuum pump. DETAILED DESCRIPTION
[0023] The following embodiments will further illustrate the present invention in conjunction with the accompanying drawings.
[0024] like Figure 5 As shown, a device used in a method for preparing an electronic slurry for multilayer ceramic capacitor electrodes includes, in sequence, an ultrasonic emulsification kettle 2, a grinder 3, a rotary vibrating screen 4, a centrifuge 5, a filter 6, a stirring kettle 7, and an evaporation concentration device connected through a pipeline 1. A peristaltic pump 8 is installed on the pipeline 1 connecting the ultrasonic emulsification kettle 2 and the grinder 3, and a peristaltic pump 8 is installed on the pipeline 1 connecting the rotary vibrating screen 4 and the centrifuge 5.
[0025] The evaporation concentration device includes a heating kettle 9, a condenser 10, a storage tank 11, and a vacuum pump 12 which are connected in sequence through a pipeline 1.
[0026] The outer layer of the ultrasonic emulsification kettle 2 is provided with a jacket 2 - 1 to cool and control the emulsification temperature of the slurry in the ultrasonic emulsification kettle 2 .
[0027] Among them, the model of ultrasonic emulsification kettle 2 is LEGEE-WZLG22116, the model of grinder 3 is DBM7L, the model of rotary vibration screen 4 is ZSΦ500-1, the model of centrifuge 5 is GQ105RS, the model of filter 6 is cobetter19-187-1, the model of stirring kettle 7 is LEGEE-WZLG230411, the model of peristaltic pump 8 is WG6005, the model of heating kettle 9 is XHSG-100L, and the model of vacuum pump 12 is 2XZ-2. The models not mentioned in the above device structures are also prior art.
[0028] Example 1 (reference Figure 5 ) 1. The PVD method was used to prepare the ultrafine nickel powder, and the BET measurement showed that the equivalent particle size was 225 nm. Propanol was added to the ultrasonic emulsification kettle, and the ultrafine nickel powder was added. Ethyl cellulose (molecular weight 148) was added, and the mixture was ultrasonically emulsified and dispersed at 12°C for 3 hours. The mixture was emulsified uniformly and adjusted to an emulsion slurry with a viscosity of 5.5 cps and a solid content of 5.3 wt%; 2. The electronic slurry after emulsification and dispersion is sent to the grinder through a peristaltic pump for grinding and dispersion. The grinder uses 1.8mm zirconium beads and the grinding temperature is 6.5℃. After grinding for 2.75h at 2850r / min, it is sieved through a 100-mesh rotary vibrating sieve to form a uniform homogeneous emulsion; 3. The screened electronic slurry is sent to a tubular centrifuge for classification through a peristaltic pump. The centrifuge speed is adjusted by frequency conversion. The centrifuge drum rotates at a high speed of 5000r / min, and the separation factor is 15000. Excessive particles are removed, and nickel powder slurry with uniform particle size distribution is obtained after overflow. The maximum particle DMax of the slurry is 0.68μm according to PSD test; 4. The graded nickel powder slurry is sent to the filter through a peristaltic pump for filtration. The slurry is filtered through a 1.5 μm pore filter element to remove foreign matter and powder clumps; 5. The filtered slurry is separated into solid and liquid by sedimentation, and the concentration is controlled at 35%. Ethanol solvent is added to the stirring kettle at a concentration of 45%. After stirring for 0.5 hours, solid and liquid are separated by sedimentation. The upper clear liquid is pumped out, and ethanol solvent is added again. Stirring and replacement are repeated three times until the carbon content of the slurry is ≤2% and the slurry viscosity is ≤20cps; 6. DHTA is added to the replaced nickel powder slurry to prepare an electronic slurry with a concentration of 30wt% and sent to a heating concentration kettle for distillation and concentration under vacuum. The pressure in the heating kettle is pumped to 90Kpa by a vacuum pump. The slurry temperature in the kettle is controlled to evaporate at 90°C. The ethanol vapor is condensed by a condenser and collected in a storage tank. After concentration, a nickel powder slurry for ceramic capacitor electrodes with a solid content of 70-73% and a metal content of 65-70% is obtained.
[0029] Example 2 (refer to Figure 5 ) 1. The PVD method was used to prepare the ultrafine nickel powder, and the BET measurement showed that the equivalent particle size was 36 nm. Ethanol was added to the ultrasonic emulsification kettle, and the ultrafine nickel powder was added. Ethyl cellulose (molecular weight was 1848) was added, and the mixture was ultrasonically emulsified and dispersed at 25°C for 3 hours. The mixture was emulsified evenly and adjusted to an emulsion slurry with a viscosity of 45 cps and a solid content of 35 wt%; 2. The electronic slurry after emulsification and dispersion is sent to the grinder through a peristaltic pump for grinding and dispersion. The grinder uses 0.1mm zirconium beads and the grinding temperature is 43°C. After grinding for 1.5 hours at 325r / min, it is sieved through a 1000-mesh rotary vibrating sieve to form a uniform homogeneous emulsion; 3. The screened electronic slurry is sent to a tubular centrifuge for classification through a peristaltic pump. The centrifuge speed is adjusted by frequency conversion. The centrifuge drum rotates at a high speed of 30,000 r / min, and the separation factor is 20,000. Excessive particles are removed, and nickel powder slurry with uniform particle size distribution is obtained after overflow. The maximum particle DMax of the slurry is 0.22 μm according to PSD test; 4. The graded nickel powder slurry is sent to the filter through a peristaltic pump for filtration. The slurry is filtered through a 0.25 μm pore size filter element to remove foreign matter and powder clumps; 5. The filtered slurry is separated into solid and liquid by sedimentation, and the concentration is controlled at 35%. Ethanol solvent is added to the stirring kettle at a concentration of 18%. After stirring for 3 hours, solid and liquid are separated by sedimentation. The upper clear liquid is removed, and ethanol solvent is added again. Stirring and replacing, until the carbon content of the slurry is ≤2% and the slurry viscosity is ≤20cps; 6. Add pineol to the replaced nickel powder slurry to prepare an electronic slurry with a concentration of 55wt% and send it into a heating concentration kettle for distillation and concentration under vacuum. The pressure in the heating kettle is pumped to 10Kpa by a vacuum pump. The slurry temperature in the kettle is controlled at 50°C for evaporation. The ethanol vapor is condensed by a condenser and collected in a storage tank. After concentration, a nickel powder slurry for ceramic capacitor electrodes with a solid content of 61-63% and a metal content of 62% is obtained.
[0030] Example 3 (reference Figure 5 ) 1. The PVD method was used to prepare the ultrafine nickel powder, and the BET measurement showed that the equivalent particle size was 125 nm. n-butanol was added to the ultrasonic emulsification kettle, and the mixture was stirred. The ultrafine nickel powder and lignin (molecular weight was 1650) were added, and the mixture was ultrasonically emulsified and dispersed at 15°C for 0.5 h. The mixture was emulsified evenly and adjusted to an emulsion slurry with a viscosity of 23 cps and a solid content of 18 wt%; 2. The electronic slurry after emulsification and dispersion is sent to the grinder through a peristaltic pump for grinding and dispersion. The grinder uses 0.5mm zirconium beads, the grinding temperature is 25°C, and after grinding for 2 hours at 1200r / min, it is sieved through a 400-mesh rotary vibrating sieve to form a uniform homogeneous emulsion; 3. The screened electronic slurry is sent to a tubular centrifuge for classification through a peristaltic pump. The centrifuge speed is adjusted by frequency conversion. The centrifuge drum rotates at a high speed of 20,000 r / min, and the separation factor is 18,000. Excessive particles are removed, and nickel powder slurry with uniform particle size distribution is obtained after overflow. The maximum particle DMax of the slurry is 0.5 μm according to PSD test; 4. The graded nickel powder slurry is sent to the filter through a peristaltic pump for filtration. The slurry is filtered through a 0.75 μm pore filter element to remove foreign matter and powder clumps; 5. The filtered slurry is separated into solid and liquid by sedimentation, and the concentration is controlled at 80%. Ethanol solvent is added to the stirring kettle at a concentration of 50%. After stirring for 1.5 hours, solid and liquid are separated by sedimentation. The upper clear liquid is pumped out, and ethanol solvent is added again. Stirring and replacement are repeated twice until the carbon content of the slurry is ≤2% and the slurry viscosity is ≤20cps; 6. Add propylene glycol to the replaced nickel powder slurry to prepare an electronic slurry with a concentration of 30wt%, and send it into a heating concentration kettle for distillation and concentration under vacuum. The pressure in the heating kettle is pumped to 50Kpa by a vacuum pump. The temperature of the slurry in the kettle is controlled to evaporate at 100°C. The ethanol vapor is condensed by a condenser and collected in a storage tank. After concentration, a nickel powder slurry for ceramic capacitor electrodes with a solid content of 70-72% and a metal content of 68-71% is obtained.
[0031] Example 4 (reference Figure 5 ) 1. The equivalent particle size of the ultrafine copper powder prepared by PVD method and measured by BET is 180nm. Acetone is added to the ultrasonic emulsification kettle, stirred, ultrafine copper powder is added, lignin (molecular weight is 509) is added, ultrasonic emulsification dispersion is performed at 25°C for 1h, emulsification is uniform, and the emulsion slurry is adjusted to a viscosity of 12cps and a solid content of 15wt%; 2. The electronic slurry after emulsification and dispersion is sent to the grinder through a peristaltic pump for grinding and dispersion. The grinder uses 1mm zirconium beads and the grinding temperature is 35°C. After grinding for 2 hours at 1000r / min, it is sieved through a 200-mesh rotary vibrating sieve to form a uniform homogeneous emulsion; 3. The screened electronic slurry is sent to a tubular centrifuge for classification through a peristaltic pump. The centrifuge speed is adjusted by frequency conversion. The centrifuge drum rotates at a high speed of 10,000 r / min, and the separation factor is 17,000. Excessive particles are removed, and nickel powder slurry with uniform particle size distribution is obtained after overflow. The maximum particle DMax of the slurry is 0.6 μm according to PSD test; 4. The graded nickel powder slurry is sent to the filter through a peristaltic pump for filtration. The slurry is filtered through a 1μm pore filter element to remove foreign matter and powder clumps; 5. The filtered slurry is separated into solid and liquid by sedimentation, and the concentration is controlled at 50%. Ethanol solvent is added to the stirring kettle at a concentration of 30%. After stirring for 2 hours, solid and liquid are separated by sedimentation. The upper clear liquid is removed, and ethanol solvent is added again. Stirring and replacement are repeated twice until the carbon content of the slurry is ≤2% and the slurry viscosity is ≤20cps; 6. Add n-butanol to the replaced copper powder slurry to prepare an electronic slurry with a concentration of 60wt% and send it into a heating concentration kettle for distillation and concentration under vacuum. The pressure in the heating kettle is pumped to 30Kpa by a vacuum pump. The slurry temperature in the kettle is controlled at 65°C for evaporation. The ethanol vapor is condensed by a condenser and collected in a storage tank. After concentration, a copper powder slurry for ceramic capacitor electrodes with a solid content of 71-74% and a metal content of 73% is obtained.
[0032] Example 5 (reference Figure 5 ) 1. The PVD method was used to prepare the ultrafine copper powder, and the BET measurement showed that the equivalent particle size was 53 nm. Ethylene glycol was added to the ultrasonic emulsification kettle, and the ultrafine copper powder was added. Lignin (molecular weight was 1513.5) was added, and the mixture was ultrasonically emulsified and dispersed at 15°C for 2 hours. The mixture was uniformly emulsified and adjusted to an emulsion slurry with a viscosity of 30-40 cps and a solid content of 35 wt%; 2. The electronic slurry after emulsification and dispersion is sent to the grinder through a peristaltic pump for grinding and dispersion. The grinder uses 0.5mm zirconium beads, the grinding temperature is 45°C, and after grinding for 3 hours at 500r / min, it is sieved through a 200-mesh rotary vibrating sieve to form a uniform homogeneous emulsion; 3. The screened electronic slurry is sent to a tubular centrifuge for classification through a peristaltic pump. The centrifuge speed is adjusted by frequency conversion. The centrifuge drum rotates at a high speed of 20,000 r / min, and the separation factor is 18,000. Excessive particles are removed, and nickel powder slurry with uniform particle size distribution is obtained after overflow. The maximum particle DMax of the slurry is 0.35 μm according to PSD test; 4. The graded nickel powder slurry is sent to the filter through a peristaltic pump for filtration. The slurry is filtered through a 0.65 μm pore size filter element to remove foreign matter and powder clumps; 5. The filtered slurry is separated into solid and liquid by sedimentation, and the concentration is controlled at 45%. Ethanol solvent is added to the stirring kettle at a concentration of 30%. After stirring for 3 hours, solid and liquid are separated by sedimentation. The upper clear liquid is removed, and ethanol solvent is added again. Stirring and replacement are repeated twice until the carbon content of the slurry is ≤2% and the slurry viscosity is ≤20cps; 6. After the replacement, sec-butanol is added to the copper powder slurry to prepare an electronic slurry with a concentration of 50wt%, which is then sent to a heating and concentrating kettle for distillation and concentration under vacuum. The pressure in the heating kettle is pumped to 20Kpa by a vacuum pump. The slurry temperature in the kettle is controlled to evaporate at 80°C. The ethanol vapor is condensed by a condenser and collected in a storage tank. After concentration, a copper powder slurry for ceramic capacitor electrodes with a solid content of 71-74% and a metal content of 70% is obtained.
[0033] Example 6 (reference Figure 5 ) 1. The PVD method was used to prepare the ultrafine copper-nickel alloy powder, and the BET measurement showed that the equivalent particle size was 240 nm. Glycerol was added to the ultrasonic emulsification kettle, stirred, and the ultrafine copper-nickel alloy powder was added. Ethyl cellulose (molecular weight was 1345) was added, and ultrasonic emulsification was performed at 20°C for 1.5 hours. The emulsification was uniform and adjusted to an emulsion slurry with a viscosity of 40-45 cps and a solid content of 28 wt%; 2. The electronic slurry after emulsification and dispersion is sent to the grinder through a peristaltic pump for grinding and dispersion. The grinder uses 2mm zirconium beads, the grinding temperature is 40°C, and after grinding for 2 hours at 300r / min, it is sieved through a 100-mesh rotary vibrating sieve to form a uniform homogeneous emulsion; 3. The screened electronic slurry is sent to a tubular centrifuge for classification through a peristaltic pump. The centrifuge speed is adjusted by frequency conversion. The centrifuge drum rotates at a high speed of 25,000 r / min, and the separation factor is 18,000. Excessive particles are removed, and nickel powder slurry with uniform particle size distribution is obtained after overflow. The maximum particle DMax of the slurry is 0.7 μm according to PSD test; 4. The graded nickel powder slurry is sent to the filter through a peristaltic pump for filtration. The slurry is filtered through a 2μm pore filter element to remove foreign matter and powder clumps; 5. The filtered slurry is separated into solid and liquid by sedimentation, and the concentration is controlled at 55%. Ethanol solvent is added to the stirring kettle at a concentration of 20%. After stirring for 3 hours, solid and liquid are separated by sedimentation. The upper clear liquid is removed, and ethanol solvent is added again. Stirring and replacement are repeated twice until the carbon content of the slurry is ≤2% and the slurry viscosity is ≤20cps; 6. Add DHTA to the replaced copper-nickel alloy powder slurry to prepare an electronic slurry with a concentration of 80wt% and send it into a heating concentration kettle for distillation and concentration under vacuum. The pressure in the heating kettle is pumped to 10Kpa by a vacuum pump. The slurry temperature in the kettle is controlled to evaporate at 90°C. The ethanol vapor is condensed by a condenser and collected in a storage tank. After concentration, a copper-nickel alloy powder slurry for ceramic capacitor electrodes with a solid content of 50-64% and a metal content of 55-61% is obtained.
[0034] The process steps in Examples 1 to 6 refer to the above examples. The specific metal powder specifications, measurements, and corresponding performance test results of the electronic paste for ceramic capacitor electrodes prepared therefrom are shown in Table 1: Table 1 Performance test results of raw powder and electronic paste for MLCC electrode prepared from it Depend on Figure 1 , Figure 2 It can be seen that in Example 3, the particle distribution in the slurry obtained after centrifugal classification is more uniform, so that Dmax is controlled within the range of less than 0.5 μm.
[0035] Depend on Figure 3 , Figure 4 It can be seen that in Example 3, foreign matter and powder lumps are basically removed after the slurry is filtered through the filter element.
Claims
1. A method for preparing an electronic paste for multilayer ceramic capacitor electrodes, characterized in that: The specific preparation steps include: (1) Ultrasonic emulsification dispersion Adding an organic solvent into an ultrasonic emulsification kettle, stirring, adding ultrafine metal powder to prepare metal slurry, then adding a thickener, ultrasonic emulsifying and dispersing, to prepare a mixed electronic slurry; (2) Grinding and dispersion The slurry dispersed by ultrasonic emulsification in step (1) is sent to a grinder for grinding and dispersion and then sieved to form a homogeneous emulsion; (3) Centrifugal classification The slurry after screening in step (2) is sent to a centrifuge for centrifugal classification to remove particles exceeding the standard, thereby obtaining an electronic slurry with uniform particle size distribution; (4) Filtering The electronic slurry after centrifugal classification in step (3) is sent to a filter for filtration to remove foreign matter and powder clumps; (5) Stirring and replacement The electronic slurry filtered in step (4) is added to a stirred tank after solid-liquid separation by sedimentation, and ethanol solvent is added for replacement to reduce the carbon content; (6) Distillation and concentration The electronic slurry after replacement in step (5) is added with an electronic solvent and then sent to an evaporation concentration device for concentration to obtain an electronic slurry for multilayer ceramic capacitor electrodes; The ultrafine metal powder in step (1) is prepared by a PVD method, and its specific surface area equivalent particle size is 30-250 nm. The ultrafine metal powder is one of nickel and copper. The organic solvent is at least one of ethanol, ethylene glycol, propanol, n-butanol, glycerol, and acetone. The thickener is lignin or ethyl cellulose (EC) with a molecular weight of 100-2000. The ultrasonic emulsification temperature is 10-25° C., and the emulsification dispersion time is 0.5-3 h. The viscosity of the prepared mixed electronic slurry is 5-45 cps, and the solid content is 5-35 wt%.
2. The method for preparing an electronic paste for multilayer ceramic capacitor electrodes according to claim 1, characterized in that: In the step (1), the ultrasonic emulsification temperature is 12-15° C., the viscosity of the prepared mixed electronic slurry is 10-25 cps, and the solid content is 7-25 wt %; the ultrafine metal powder is nickel powder, and the oxygen content of the nickel powder is 10000-55000 ppm.
3. The method for preparing an electronic paste for multilayer ceramic capacitor electrodes according to claim 1, characterized in that: In the step (2), the grinding machine uses 0.1-2 mm zirconium beads, the grinding machine speed is 300-3000 r / min, the grinding temperature is 5-45° C., the grinding time is 1.5-3 h, and the screen is 100-1000 mesh.
4. The method for preparing an electronic paste for multilayer ceramic capacitor electrodes according to claim 1, characterized in that: The electronic slurry after screening in the step (3) is sent to a tubular centrifuge for classification through a peristaltic pump. The drum speed of the tubular centrifuge is 5000-30000 r / min, and the separation factor is 15000-20000. After centrifugal classification, the electronic slurry is tested by PSD and the DMax is 0.2-0.7 μm.
5. The method for preparing an electronic paste for multilayer ceramic capacitor electrodes according to claim 1, characterized in that: The electronic slurry after centrifugal classification in step (4) is sent to a filter for filtration through a peristaltic pump, and the pore size of the filter element is 0.2-2 μm.
6. The method for preparing an electronic paste for multilayer ceramic capacitor electrodes according to claim 1, characterized in that: The electronic slurry filtered in step (5) is added to a stirring kettle, and solid-liquid separation is carried out by sedimentation, and the concentration is controlled at 30-80%, and ethanol solvent is added to a concentration of 15-50%. After stirring for 0.5-3 hours, solid-liquid separation is carried out by sedimentation, and the upper clear liquid is removed, and ethanol solvent is added for replacement until the carbon content of the slurry is ≤2% and the slurry viscosity drops to below 20cps.
7. The method for preparing an electronic paste for multilayer ceramic capacitor electrodes according to claim 1, characterized in that: In the step (6), the electronic solvent is one of DHTA, terpineol, glycerol, n-butanol, and sec-butanol. After the electronic solvent is added, the electronic slurry concentration is 30-80wt%. The electronic slurry is distilled and concentrated under vacuum. The absolute pressure in the heating concentration kettle is 10-100Kpa. The slurry temperature in the heating concentration kettle is controlled at 50-100°C. The alcohol solvent is removed by vacuum evaporation. The solvent residue is ≤5%. The solid content of the electronic slurry is 50-75%, and the metal content is 55-75%.
8. The method for preparing an electronic paste for multilayer ceramic capacitor electrodes according to claim 1, characterized in that: In the step (6), the absolute pressure in the heating and concentrating kettle is 20-80 KPa, the temperature of the slurry in the heating and concentrating kettle is controlled at 50-80°C, the residual solvent content is ≤1.5%, the solid content of the electronic slurry is 55-75%, and the metal content is 60-70%.
9. An apparatus for use in the method for preparing electronic paste for multilayer ceramic capacitors as claimed in claim 1, characterized in that: The invention comprises an ultrasonic emulsification kettle, a grinder, a rotary vibrating screen, a centrifuge, a filter, a stirring kettle and an evaporation concentration device which are connected through pipelines. A peristaltic pump is installed on the pipeline connecting the ultrasonic emulsification kettle and the grinder, and a peristaltic pump is installed on the pipeline connecting the rotary vibrating screen and the centrifuge.
10. The device used in the method for preparing electronic paste for multilayer ceramic capacitors according to claim 9, characterized in that: The evaporation concentration device comprises a heating kettle, a condenser, a storage tank and a vacuum pump which are sequentially connected through pipelines. The condenser can recover and reuse evaporated ethanol vapor.
Citation Information
Patent Citations
External electrode slurry for multilayer ceramic capacitor and preparation method of external electrode slurry
CN114783770A
Method for producing composite powder and conductive thick film paste and multilayer ceramic electronic component using composite powder obtained by the production method
JP2015083714A